2019
DOI: 10.1123/ijsnem.2018-0165
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Rapid Weight Loss and Rapid Weight Gain in Combat Sport Athletes Preparing for Competition: A Systematic Review

Abstract: 1 2 Combat sport athletes typically engage in a process called making-3 weight, characterised by rapid weight loss (RWL) and subsequent 4 rapid weight gain (RWG) in the days preceding competition. These 5 practices differ across each sport, but no systematic comparison of the 6 size of the changes in body mass exists. The aim was to determine the 7 magnitude of RWL and RWG in combat sport athletes preparing for 8 competition. The review protocol was preregistered with PROSPERO 9 [CRD42017055279]. In eligible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 52 publications
5
64
1
1
Order By: Relevance
“…RWL refers to the strategy adopted by most combat sports athletes to temporally reduce their body mass, typically about 2-10%, but with reports of reductions greater than 12% [23,24], a few days before competitions to fit in a lower weight category, in an attempt to gain an advantage against lighter, smaller, and weaker opponents [22]. Achieved only through the combination of aggressive dehydration and starvation methods [24][25][26][27][28], it is a well-established common practice among combat sports athletes [29] whose harmful effects are already known and well documented in the literature [26,[30][31][32][33]. RWL is not an issue restricted to adult or professional sports as children and adolescents from 10 years old also use RWL for competitive advantage [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…RWL refers to the strategy adopted by most combat sports athletes to temporally reduce their body mass, typically about 2-10%, but with reports of reductions greater than 12% [23,24], a few days before competitions to fit in a lower weight category, in an attempt to gain an advantage against lighter, smaller, and weaker opponents [22]. Achieved only through the combination of aggressive dehydration and starvation methods [24][25][26][27][28], it is a well-established common practice among combat sports athletes [29] whose harmful effects are already known and well documented in the literature [26,[30][31][32][33]. RWL is not an issue restricted to adult or professional sports as children and adolescents from 10 years old also use RWL for competitive advantage [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Kasper et al [5] followed an MMA athlete who lost 18.1% (14.5 kg) body mass over eight weeks; including a reduction of 9.3% (7.3 kg) in the final 24-hours, which induced blood values consistent with hypernatremia and acute kidney injury. While extreme, this case not unique and MMA has experienced two RWL-related fatalities in recent years [4]. Both were associated with severe dehydration achieved via potentially harmful methods such as sauna use, training in sweat (rubber) suits, and use of diuretics: all commonly used RWL methods in MMA [6].…”
Section: Introductionmentioning
confidence: 89%
“…Although making weight is ubiquitous across combat sports, MMA athletes undergo the greatest changes in body mass for competition [3,4]. Kasper et al [5] followed an MMA athlete who lost 18.1% (14.5 kg) body mass over eight weeks; including a reduction of 9.3% (7.3 kg) in the final 24-hours, which induced blood values consistent with hypernatremia and acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Making weight is characterized by a rapid weight loss (RWL) period and a subsequent rapid weight gain (RWG) in the days before competition [ 7 ]. These practices differ across each sport, depending on the distance between the weighting procedure and the match, so the RWL could start 2–3 days before the competition and the RWG could last from 1 to 18 h [ 8 ]. It has been reported that combat sports athletes have performed this practice at least once in life [ 9 , 10 ], but this methodology is also known among amateur fighters and it is applied from two to eight times per year (personal communication and experience within the Italian Muay Thai and Italian Boxing federations).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that combat sports athletes have performed this practice at least once in life [ 9 , 10 ], but this methodology is also known among amateur fighters and it is applied from two to eight times per year (personal communication and experience within the Italian Muay Thai and Italian Boxing federations). The goal of cutting weight is to be able to compete in a lower-weight category than one of the regular season, which would translate into a physical advantage; notwithstanding, scientific literature has demonstrated a reduction in sports and psychological performance after drastic RWL and RWG [ 8 , 11 ]. The issues of the making weight practice encompass not only the frequency over the year but also that is operated based on anecdotes and non-professional supervision, which have called the attention of health professionals due to the alarming potential adverse events [ 12 ].…”
Section: Introductionmentioning
confidence: 99%